2011
DOI: 10.1007/s11182-011-9529-z
|View full text |Cite
|
Sign up to set email alerts
|

Deformation behavior and spall fracture of the Hadfield steel under shock-wave loading

Abstract: Comparative studies of regularities in plastic deformation and fracture of the Hadfield polycrystalline steel upon quasi-static tension, impact failure, and shock-wave loading with rear spall are performed. The SINUS-7 accelerator was used as a shock-wave generator. The electron beam parameters of the accelerator were the following: maximum electron energy was 1.35 MeV, pulse duration at half-maximum was 45 ns, maximum energy density on a target was 3.4⋅10 10 W/cm 2 , shock-wave amplitude was ~20 GPa, and stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…For example, the cooling rates have been calculated [9,[25][26][27]and investigated experimentally [28] to be of the order of 10 8 -10 9 K/s. Such a drastic temperature variation induces the formation of thermal stresses and shock waves reaching several hundreds of Mpa, which would induce severe surface deformation the materials [29][30][31][32][33].With repeated heating and cooling induced by successive pulsed electron beams irradiation, it has been observed that precipitates are partially or completely dissolved and that chemistry segregations are drastically reduced in the top surface melted layer where supersaturated solid solution can form [34,35].These microstructural changes improve the corrosion resistances of the surface layer which has been established in various alloys such as steels [34][35][36][37], Mg alloys [38][39][40]and Al alloys [41].Besides, due to the effect of dynamic stress fields induced by the drastic thermal processes on the material, plastic deformation occurs at the treated surface and subsurface layers, resulting in surface and subsurface microhardness enhancement [30,37,42].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the cooling rates have been calculated [9,[25][26][27]and investigated experimentally [28] to be of the order of 10 8 -10 9 K/s. Such a drastic temperature variation induces the formation of thermal stresses and shock waves reaching several hundreds of Mpa, which would induce severe surface deformation the materials [29][30][31][32][33].With repeated heating and cooling induced by successive pulsed electron beams irradiation, it has been observed that precipitates are partially or completely dissolved and that chemistry segregations are drastically reduced in the top surface melted layer where supersaturated solid solution can form [34,35].These microstructural changes improve the corrosion resistances of the surface layer which has been established in various alloys such as steels [34][35][36][37], Mg alloys [38][39][40]and Al alloys [41].Besides, due to the effect of dynamic stress fields induced by the drastic thermal processes on the material, plastic deformation occurs at the treated surface and subsurface layers, resulting in surface and subsurface microhardness enhancement [30,37,42].…”
Section: Introductionmentioning
confidence: 99%